Experimental and numerical investigations on the vertical propagation of hydraulic fractures in laminated shales. (23rd May 2018) - Shan, Qinglin; Jin, Yan; Tan, Peng; Zhang, Ruxin
Abstract: Bedding structure and strong tectonic compression of deep shale reservoirs have a great influence on the vertical propagation of hydraulic fractures and proppant transportation, posing a severe challenge for the hydraulic fracturing design. A combined experimental and numerical study was carried out to investigate the vertical propagation of hydraulic fractures in laminated shales. As a supplement to the physical experiment method, a flow-stress-displacement-damage coupling method based on continuum mechanics was developed, which can effectively simulate complex hydraulic fracture geometries observed in mining experiments. The validity of the numerical method was verified by experiment results. The experiment and simulation results show that: (1) strong horizontal tectonic compression is not favorable for hydraulic fractures to pass through bedding planes; (2) the decrease of bedding interface strength and increase of bedding dip angle will cause hydraulic fracture diversion, offset and containment; (3) increasing the viscosity of the fracturing fluid can reduce the filtration loss of fracturing fluid into beddings, and improve the ability of hydraulic fractures to penetrate bedding planes in various unfavorable conditions; (4) under the same geo-stress condition, increasing the injection rate of fracturing fluid can promote the penetration of beddings with low dip angles, but the high injection rate may lose its role when low viscosity fluid is used under conditions of high tectonic compression and high bedding dip angles (over 30°). In such conditions, fracturing fluid with higher viscosity and low damage to reservoirs is recommended.